Effects of alumina nanoparticles on the microstructure, strength and wear resistance of poly(methyl methacrylate)-based nanocomposites prepared by friction stir processing. (March 2018) - Aghajani Derazkola, Hamed; Simchi, Abdolreza
Abstract: In this study, alumina-reinforced poly(methyl methacrylate) nanocomposites (PMMA/Al2 O3 ) containing up to 20 vol% nanoparticles with an average diameter of 50 nm were prepared by friction stir processing. The effects of nanoparticle volume fraction on the microstructural features and mechanical properties of PMMA were studied. It is shown that by using a frustum pin tool and employing an appropriate processing condition, i.e. a rotational speed of 1600 rpm/min and transverse velocity of 120 mm/min, defect free nanocomposites at microscale with fine distribution of the nanoparticles can successfully been prepared. Mechanical evaluations including tensile, flexural, hardness and impact tests indicate that the strength and toughness of the material gradually increases with the nanoparticle concentration and reach to a flexural strength of 129 MPa, hardness of 101 Shore D, and impact energy 2 kJ/m 2 for the nanocomposite containing 20 vol% alumina. These values are about 10% and 20% better than untreated and FSP-treated PMMA (without alumina addition). Fractographic studies indicate typical brittle features with crack deflection around the nanoparticles. More interestingly, the sliding wear rate in a pin-on-disk configuration and the friction coefficient are reduced up to 50% by addition of alumina nanoparticles. The worn surfaces exhibit typical sliding and ploughing features.